Effects of Equipment-Structure-Soil Interaction on Seismic Response of Equipment and Structure via Real-Time Dynamic Substructuring Shaking Table Testing - Chongxiang Zhang; Nan Jiang (Shock and Vibration)
Equation of motion for an equipment-structure-soil (ESS) interaction system was derived using the branch substructure method. After rearrangement, this equation was applied to real-time dynamic substructuring shaking table (RTDSST) testing of the ESS system. This method adopts the equipment-structure (ES) subsystem as the experimental substructure and a modal reduced soil model as the numerical substructure: the former is tested via the shaking table, and the latter is numerically simulated, while real-time data communication occurs between the two substructures during testing. A scale model of the ESS system was designed and underwent an RTDSST test. The experimental data were found to be consistent with the numerical calculation results, which corroborates the reliability and validity of the proposed testing method. A comparison of the experimental results from different earthquake stages implies that seismic responses of the equipment and structure decreased in general due to the intervention of soil, but the soil effect weakened with earthquake intensity.